Diagnosing and treating Krukenberg tumor: a gynecologist’s dilemma - Chandradas, Danu; Thomas, Betsy; Jayachandran, Abhilash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Krukenberg tumor is a rare tumor of ovary. It is a metastatic ovarian tumor usually from a primary in gastrointestinal tract. The lesions are usually not discovered until primary disease is advanced and therefore most patients die within a year. In some cases primary is never found and their prognosis worsens. We are reporting a case on which right ovariotomy was done for a complex right ovarian mass from another hospital. Even after surgery her symptoms persisted and on further evaluation, she was found to have primary gastric carcinoma with carcinoma of recto sigmoid and left Krukenberg tumor. Here the diagnosis of a metastatic disease was missed during the initial evaluation. 80% of these tumors are bilateral and usually both ovaries are affected at the same time. But in this case, left ovary was normal which later increased in size within just 2 weeks. No optimal treatment strategy is clearly mentioned in literature. Whether to give her a palliative care or a definitive cytoreductive surgery was debated. Recent literature says that if we can render the patient free of gross residual disease, we should do a primary debulking surgery rather than palliative care. Many studies have shown that aggressive debulking of macroscopic disease improves the survival rate.